Financial Times mastering marketing the complete MBA companion in marketing (Financial Times mastering series., 1999)
Geared to the MBA student, a comprehensive guide to marketing philosophy, strategy, and technique prepares would-be business leaders for the marketing realities of the 21st century. Original.